Singles - Cameron, Crowe; Bridget, Fonda; Campbell Scott; Kyra Sedgwick; Sheila Kelley; Jim TrueFrost; Matt Dillon; Bill Pullman (USA Atkinson/Knickerbocker Productions, 1992)
A group of twenty-something friends, most of whom live in the same apartment complex, search for love and success in grunge-era Seat
Love is a game. Easy to start. Hard to finish.
Cameron Crowe
Languages : English, German, Spanish
Subtitles : English, Turkish, French, Italian, Hebrew, Icelandic
Keywords: Comedy; Drama; Romance